The Effect of Job Stress on the Performance of Cleaning Service Employees at Besemah Regional General Hospital, Pagar Alam City - Putri Wahyuni; Yuliansyah M.Diah; Nurlela Nurlela (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to examine the Influence of Work Stress on the Performance of Cleaning Service Employees at Besemah Regional General Hospital in Pagar Alam City. The sampling method used is a non-probability method with a Saturated Sampling/Census Technique. The sample in this study consists of 76 people from the Cleaning Service Employees at Besemah Regional General Hospital in Pagar Alam City. Based on the results of quantitative analysis, including validity and reliability tests, classical assumption tests, hypothesis tests using t-tests, and analysis of the coefficient of determination (R2). The data analysis technique used is simple linear regression analysis. Qualitative analysis is an interpretation of the data obtained in the study as well as the results of data processing that has been carried out by providing information and explanations. Data that have passed the validity test, reliability test, and classical assumption test are processed to produce the following regression equation: Y = 4.424 + 0,137X +e That the constant value is 4.424. This means that if the Work Stress variable (X) is absent or equals zero, then the value of the Cleaning Service Employee Performance at Besemah Regional General Hospital in Pagar Alam City is 4.424. The Work Stress Coefficient value (X) is 0.137. This indicates that the Employee Additional Income variable has a positive effect on the Cleaning Service Employee Performance at Besemah Regional General Hospital in Pagar Alam City. The hypothesis testing shows that Work Stress has a positive and significant effect on the Cleaning Service Employee Performance at Besemah Regional General Hospital in Pagar Alam City because the calculated t-value with the resulting significance is 0.000 < 0.05. This indicates that Work Stress has a positive influence or the Work Stress variable is 0.137, so the magnitude of the Work Stress influence is 13.7%. Using the t-test, it shows that the Work Stress variable is proven to significantly affect the dependent variable, which is the Improvement of Cleaning Service Employee Performance at Besemah Regional General Hospital in Pagar Alam City (Y).